Rediscovery of Heinrich's Nightjar Eurostopodus diabolicus - K David Bishop; Jared M Diamond (Indonesian Ornithologists’ Union, 1997)
Sulawesi, the largest island of Wallacea, Indonesia, supports a rich and distinctive avifauna that includes 10 endemic genera and 41 species (White & Bruce 1986, Coates & Bishop in press). Among the least known of these endemics is Heinrich's Nightjar Eurostopodus diabolicus (Caprimulgidae) (or Diabolical and/or Satanic Nightjar in some recent literature), known previously only from the unique type (Stresemann 1931, 1940). We now report its rediscovery and field observations.